2006
DOI: 10.1074/jbc.m601356200
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of IscA and IscU in Biogenesis of Iron-Sulfur Clusters

Abstract: Increasing evidence suggests that sulfur in ubiquitous ironsulfur clusters is derived from L-cysteine via cysteine desulfurases. In Escherichia coli, the major cysteine desulfurase activity for biogenesis of iron-sulfur clusters has been attributed to IscS. The gene that encodes IscS is a member of an operon isc-SUA, which also encodes two highly conserved proteins: IscU and IscA. Previous studies suggested that both IscU and IscA may act as the iron-sulfur cluster assembly scaffold proteins. However, recent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
92
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 58 publications
6
92
0
Order By: Relevance
“…Hence, we might expect a great diversity in the way bacteria make use of otherwise conserved components to carry out Fe-S biogenesis. Another challenge to the view of A-type proteins as scaffolds comes from in vitro investigations, which concluded that A-type proteins could be simple iron donors (30)(31)(32)(33)(34). Interestingly, the erpA gene is part of a chromosomal region that is particularly rich in iron uptake-related genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we might expect a great diversity in the way bacteria make use of otherwise conserved components to carry out Fe-S biogenesis. Another challenge to the view of A-type proteins as scaffolds comes from in vitro investigations, which concluded that A-type proteins could be simple iron donors (30)(31)(32)(33)(34). Interestingly, the erpA gene is part of a chromosomal region that is particularly rich in iron uptake-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…Three conserved Cys residues could act as ligands for these clusters, as indicated by mutagenesis studies and by the recently obtained 3D structure of IscA (26)(27)(28)(29). However, the proposal that IscA/SufA acts as a scaffold was challenged by in vitro studies, which suggest that A-type proteins act as iron chaperones, and by the fact that mutations in iscA or sufA did not yield major physiological defects (30)(31)(32)(33)(34)(35)(36). Noticeably, however, in A. vinelandii, iscA appeared to be required at high concentrations of oxygen (37).…”
mentioning
confidence: 99%
“…Interestingly, competition experiments indicate that IscU rather than IscA preferentially forms an Fe-S cluster when both proteins are mixed simultaneously with IscS, iron, and cysteine. In contrast, IscA appears to bind iron much more tightly than IscU does if cysteine is omitted (132). A similar "iron-first" stepwise model of cluster assembly has been proposed for SufU (referred to as IscU in the cited work), based on its ability to bind iron with a high affinity (87).…”
mentioning
confidence: 99%
“…Recent studies also indicated that L-cysteine could mobilize the iron center in IscA for Fe-S cluster assembly on IscU, whereas biologically related thiols such as N-acetyl-L-cysteine or reduced glutathione failed to mobilize the iron center (25). Based on these experiments, IscA was proposed to act as an iron chaperone that binds free iron for donation to IscU (132).…”
mentioning
confidence: 99%
“…DsrR resembles the protein IscA, which is involved in iron-sulfur cluster maturation. IscA functions either as an iron chaperone, delivering iron ions to nascent iron-sulfur clusters built on the IscU scaffold (21,67), or as an alternative scaffold for [2Fe-2S] or [4Fe-4S] clusters (37,49). Sequence alignments of several DsrR homologues of sulfuroxidizing bacteria with IscA homologues of non-sulfur-oxidizing bacteria illustrate the sequence similarity between these proteins but also highlight the differences between them (Fig.…”
Section: Monomeric Dsrr Does Not Have the Iron-or Fe-s-bindingmentioning
confidence: 99%